Base de datos centralizada para sistemas de seguridad - Valdivieso A., Carlos (2009)
Centralized databases (Client -Server Model) are widely used because of the benefits they provide, its main characteristic is the fact that they can store data in one place, preserving its integrity and consistency. This paper contains the design and implementation of a centralized database for managing, a graphical interface developed in LabView from National Instruments (graphical tool for designing applications for data acquisition), the information captured by the following Security Systems: Home Security System, Industrial Security System, System Lab Safety, Security System for Laboratory Equipment, Vehicle Security System, Control System for Personnel, Security System for main entrance and corridors. All these projects were part of a Graduation Subject "Advanced Microcontrollers". It is possible to say that the database will support several other security systems containing sensors, actuators and agents supported centralized database.